Organic’s living pharmacy plants cultivating in Dorema Nusantara orphanage as a repressive step in inhibiting the expansion of Coronavirus transmission in North Sumatera Province - Situmorang, Sawitania; Sipayung, Rosita; Tanjung, Lindawati; Sebayang, Thomson; Sigalingging, Riswanti (Talenta Publisher, 2020)
The Covid-19 pandemic has had a major impact on human life around the world in various aspects of life, including Indonesia. Health and economy are two sectors that gave a greatest impact on societies’ life. As the result, agricultural activity become returning to be excellent considering while many other secondary and tertiary sectors are paralyzed by the presence of this virus. One of the promising agricultural commodities among all for planting at this time is spices such as ginger and turmeric because of their advantage as immunity boosters. Available in quite comprehensive space of agricultural land in Indonesia, North Sumatera is still potential to be planted. Among the various effected communities, Dorema Nusantara orphanage that located in Medan Helvetia district, Deli Serdang Regency was choosen as location for this community service activity with considering that the respondents was the one who received a heavily affect by this pandemic. The activity used organic cultivation method because of the abundant availability of raw materials for litter and household waste around this place. Respondents were very enthusiastic about participating in this activity. They also hope that this activity can take place in a sustainable manner.